1988
DOI: 10.1111/j.1471-6402.1988.tb00978.x
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Sequelae of Abortion: Implications for Clinical Practice

Abstract: The literature is summarized on normative reactions to abortion and factors that increase risk of negative emotional sequelae. Four areas of inquiry for identifying psychotherapeutic issues in regard to abortion are elaborated, including: (a) characteristics of the woman prior to and at the time of the abortion, (b) the nature of social support and the cultural milieu around the abortion, (c) characteristics of the medical environment and abortion procedure, and (d) events subsequent to the abortion which may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“…Baker and Khasiani (1992) expressed concern about the lack of information and absence of counselling in non-legal settings. It has been suggested that a woman's reaction to abortion may be influenced by whether or not she receives counselling and by the type of counselling she receives (Lemkau, 1988). Clearly, in contexts where abortion is illegal, the provision of counselling interventions is limited, if not non-existent.…”
Section: Treatment By Abortion Providermentioning
confidence: 98%
See 2 more Smart Citations
“…Baker and Khasiani (1992) expressed concern about the lack of information and absence of counselling in non-legal settings. It has been suggested that a woman's reaction to abortion may be influenced by whether or not she receives counselling and by the type of counselling she receives (Lemkau, 1988). Clearly, in contexts where abortion is illegal, the provision of counselling interventions is limited, if not non-existent.…”
Section: Treatment By Abortion Providermentioning
confidence: 98%
“…Lemkau (1988) suggested that decisions about childrearing, or about pursuing the options that "limit childbearing, are of such consequence, that ambivalence is the norm. Participants' descriptions highlighted the experience that there is no painless way of dealing with an unwanted pregnancy.…”
Section: Personal Reasonsmentioning
confidence: 98%
See 1 more Smart Citation
“…When women freely choose legal abortions, they usually cope quite well. Negative emotional aftereffects are uncommon; the most frequently reported emotion is relief (Lemkau, 1988). Researchers have generally found that psychological distress scores drop immediately after abortions and remain low for several weeks afterward.…”
Section: Abortionmentioning
confidence: 98%
“…Ambivalence and anxiety before the procedure has been reported in previous studies. Indeed, Lemkau [10] claims that ambivalence is the norm for a woman who has an abortion, despite liberalisation of abortion laws, and that it is conceptualised in intrapsychic terms as 'personal conflict' , her decision being in conflict with her personal values. [11,12] The fact that women in this survey seemed relieved and objectively euthymic (as revealed by the completed PTSD and depression screening instruments), yet admitted to depressed mood/suicidal ideation/ conflicted emotions, emphasises the subjective experience of the TOP.…”
mentioning
confidence: 99%